ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI PENGANGGURAN TERDIDIK LULUSAN PERGURUAN TINGGI JAWA TIMUR - Faramadina, Dinda amalia; Fadjar, Nurman Setiawan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
One of the characteristics of unemployment in Indonesia is the large number of unemployed with a higher education background which is called educated unemployment. There was an increase in educated unemployment in Indonesia and East Java Province during 2018 – 2020. This study aims to analyze the factors of educated unemployment for East Java university graduates. With primary data and binary logit regression model to determine the effect of age, gender, level of education, reservation wage, and work skills on unemployed educated East Java university graduates. Which causes age to have a negative effect on educated unemployment, while wages have a positive effect on educated unemployment. In addition, two factors of job skills, career development learning and problem solving skills have a negative influence on educated unemployment. The results of the study indicate that unemployed youth are men and women with college education, and expect high levels of wages.